1999
DOI: 10.1099/13500872-145-5-1123
|View full text |Cite
|
Sign up to set email alerts
|

Purification of geranylgeranyltransferase I from Candida albicans and cloning of the CaRAM2 and CaCDC43 genes encoding its subunits

Abstract: All previously characterized protein geranylgeranyltransferases I (GGTase I) are heterodimeric zinc metalloenzymes which catalyse geranylgeranylation of a cysteine residue in proteins containing a C-terminal CaaL motif (C, Cys; a, aliphatic amino acid; L, Leu). The a and /?subunits of GGTase I of Saccharomyces cerevisiae are encoded by RAM2 and CDC43, respectively, and are essential for yeast viability. The authors are therefore investigating the role of geranylgeranylation in the related pathogenic yeast, Can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
19
0

Year Published

2000
2000
2014
2014

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 43 publications
0
19
0
Order By: Relevance
“…Rho1p and Cdc42p of C. albicans contain CaaL motifs and are likely GGTase I substrates in vivo (22,28). Previously, we reported the purification of C. albicans GGTase I and the cloning and sequence analysis of its ␣ and ␤ subunit genes (27). Our work showed that C. albicans GGTase I is also a zinc-dependent, magnesium-dependent heterodimer whose subunits demonstrated 30% amino acid identity with their human counterparts.…”
mentioning
confidence: 92%
See 3 more Smart Citations
“…Rho1p and Cdc42p of C. albicans contain CaaL motifs and are likely GGTase I substrates in vivo (22,28). Previously, we reported the purification of C. albicans GGTase I and the cloning and sequence analysis of its ␣ and ␤ subunit genes (27). Our work showed that C. albicans GGTase I is also a zinc-dependent, magnesium-dependent heterodimer whose subunits demonstrated 30% amino acid identity with their human counterparts.…”
mentioning
confidence: 92%
“…Protein PTase activities were determined by an acid quench-filtration assay as previously described (27) All reactions were performed in duplicate and were initiated by the addition of PTase activity (2.5 to 5 l) to a final volume of 25 l and incubated at 30°C for 30 to 60 min. All other details of the assay and the origin of the Ras substrates were described previously (27).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…In pathogenic microorganisms, such as C. albicans, disruption of protein prenylation of such essential cellular proteins has the potential for the development of new antifungal medications (5)(6)(7)(8)23). The Ram2 gene in C. albicans encodes the common ␣-subunit of FTase and GGTase-I; knock-out mutations of this gene are lethal (5).…”
mentioning
confidence: 99%